Ethyl acetate extract of Terminalia chebula alleviates DSS-induced ulcerative colitis in C57BL/6 mice - Dong, Wan-Rong; Li, Yao-Yao; Liu, Tian-Tian; Zhou, Gao; Chen, Yu-Xin (Frontiers in Pharmacology, 2023)
The Chinese pharmacopeia records Terminalia chebula as effective in treating prolonged diarrhea and dysentery, blood in the stool, and prolapse. Modern pharmacological research proves it has multiple pharmacological benefits, including antioxidant, anti-inflammatory, analgesic, hepatoprotective, neuroprotective, and other properties.Objectives: This study aims to clarify the role of Terminalia chebula's ethyl acetate extract (TCEA) on ulcerative colitis (UC) induced by dextran sodium sulfate (DSS) in mice, as well as explore the potential mechanism of action.The variation of different extracts of Terminalia chebula was detected using the HPLC technique, and the main components in TCEA were identified. DSS was used to establish a mouse model to mimic the physiological state of UC in humans; the alleviating effect of TCEA and positive control 5-ASA on UC mice were evaluated by gavage treatment. Disease progression was assessed by monitoring the mouse's weight change and disease activity index (DAI). The changes in colon tissue were estimated by measuring colon length, HE, and AB-PAS staining and detecting oxidative stress parameters. The results draw from Western blot and real-time PCR showed the TLR4/MyD88/NF-κB pathway may involve in the anti-inflammatory activity of TCEA. Furthermore, the gut flora sequencing technique was employed to monitor the differentiation of intestinal microbiota of mice induced by DSS and TCEA treatment.Results: TCEA significantly lowered DAI scores and inhibited the weight loss and colonic shortening induced by DSS. The colon histomorphology and oxidative stress levels were enhanced after TCEA treatment compared with DSS induced UC group. TCEA attenuated the inflammatory response by regulating TLR4/MyD88/NF-κB pathway activation. Intestinal flora sequencing showed that DSS and TCEA greatly impacted mice's composition and diversity of intestinal microorganisms. But TCEA increased the abundance of Bacteroidetes and decreased the abundance of Firmicutes and Proteobacteria compared with the DSS group, which contributed a lot to returning the intestinal flora to a balanced state.This study confirms the alleviating effect of TCEA on UC and provides new ideas for developing TCEA into a new drug to treat UC.